Barriers and Challenges of Computing Students in an Online Learning Environment: Insights from One Private University in the Philippines - Fabito, Bernie S.; Trillanes, Arlene O.; Sarmiento, Jeshnile (International Journal of Computing Sciences Research; Vol 5 (2021): Vol 5, 2020)
Purpose – While the literature presents various advantages of using blended learning, policymakers must identify the barriers and challenges faced by students that may cripple their online learning experience. Understanding these barriers can help academic institutions craft policies to advance and improve the students' online learning experience. This study was conducted to determine the challenges of computing students in one private University in the Philippines during the period where the entire Luzon region was placed under the Enhanced Community Quarantine (ECQ) as a response to the COVID-19 pandemic.  Method – A survey through MS Forms Pro was performed to identify the experiences of students in online learning. The survey ran from March 16 to March 18, 2020, which yielded a total of 300 responses. Results – Descriptive statistics revealed that the top three barriers and challenges encountered by students were 1.) the difficulty of clarifying topics or discussions with the professors, 2.) the lack of study or working area for doing online activities, and 3.) the lack of a good Internet connection for participating in online activities. Conclusion – It can be concluded that both students and faculty members were not fully prepared to undergo full online learning. More so, some faculty members may have failed to adapt to the needs of the students in an online learning environment. Recommendations – While the primary data of the study mainly came from the students, it would also be an excellent addition to understand the perspective of the faculty members in terms of their experiences with their students. Their insights could help validate the responses in the survey and provide other barriers that may not have been included in the study.  Practical Implications – The study has revealed gaps in online learning as experienced by the computing students, which can help the management craft a holistic framework encompassing both the learners and teachers for a successful online learning experience for the students.